Identification of fluocinolone acetonide to prevent paclitaxel‐induced peripheral neuropathy. Issue 3 (September 2016) - Cetinkaya‐Fisgin, Aysel; Joo, Min Geol; Ping, Xiang; Thakor, Nitish V.; Ozturk, Cengizhan; Hoke, Ahmet; Yang, In Hong
Abstract: Paclitaxel (PTX) is among the most commonly used cancer drugs that cause chemotherapy‐induced peripheral neuropathy (CIPN), a debilitating and serious dose‐limiting side effect. Currently, no drugs exist to prevent CIPN, and symptomatic therapy is often ineffective. In order to identify therapeutic candidates to prevent axonal degeneration induced by PTX, we carried out a phenotypic drug screening using primary rodent dorsal root ganglion sensory neurons. We identified fluocinolone acetonide as a neuroprotective compound and verified it through secondary screens. Furthermore, we showed its efficacy in a mouse model of PTX‐induced peripheral neuropathy and confirmed with four different cancer cell lines that fluocinolone acetonide does not interfere with PTX's antitumor activity. Our study identifies fluocinolone acetonide as a potential therapy to prevent CIPN caused by PTX.